User Orientation in University Libraries - Iyengar, T. K. S. (Journal of Information and Knowledge, 2014)
User orientation in academic libraries is becoming an important area where better understanding and exploitation of the academic environment in which the library exists are possible through the development of methods by which the library can respond better to the needs of the environment. Educating the user in an academic environment should be the ultimate goal of achievement by the academic librarian. It is helpful to examine periodically the pattern of incidence of different kinds of questions put by different categories of readers at different periods of time. In addition to mentioning the need for orientation of users, methods of orientation and level of orientation, the paper also presents data on the impact of orientation on users at the end of an academic session. As a case study, the data on the Indian Institute of Science Library, are analysed in different ways and studied in greater detail both in pre-orientation and post-orientation periods. In the end, an attempt is made to highlight the work done and achievements of the country in the subject, how the programs are being adopted to meet the changing needs of the country and some areas of cooperation between India and the U.S.A are identified.